Intensity of Senior High School Students using Local Language in daily life - Yusri, Yusri; R., Mantasiah; Hasmawati, Hasmawati; Azizah, Laelah (Indonesian Journal of Educational Studies, 2020)
Abstract. This study used a survey approach which aims to examine how the intensity of the use of local language in high school students.  Participants were high school students who were selected purposively by considering gender (50% boys and 50% girls) and the area of residence (50% suburban area and 50% rural area).  The research instrument used was in the form of 3 survey questions consisting of 1) how often to use local languages in schools, 2) how often to use local languages in the community, and 3) how often to use local languages in the family. The data collection process is carried out online using the google form platform.  The verified data were analyzed using descriptive statistical methods and inferential statistics using the SPSS 26 application. Finding show that 1) students in urban areas use local languages less  than students in rural area, 2) students use more local languages in the home environment than in the school environment and social environment, 3) there is no significant difference in the use of local languages between male students and female students. It can  be concluded that gender is not a factor affecting language attitudes for the context of using local languages.